Laparoscopic Tubal Ligation Under Peritoneal Lavage Anesthesia. Issue 1 (January 1985) - Deeb, Ramon J.; Viechnicki, Bruce M.
Abstract : A technique is described utilizing peritoneal lavage with lidocaine for the purpose of laparoscopic tubal occlusion. The technique provided quite acceptable operating conditions. There was ready acceptance by all selected patients. Intraoperative and postoperative complications were quite low and readily treatable. The technique, while obviously not new in anesthetic practice, is new for laparoscopy and provides, in the authors' opinions, an acceptable alternative to general, spinal, and epidural anesthesia.